Proteomic investigations into hypertension: what's new and how might it affect clinical practice?. (3rd July 2019) - Corbacho-Alonso, N.; Rodríguez-Sánchez, E.; Martin-Rojas, T.; Mouriño-Alvarez, L.; Sastre-Oliva, T.; Hernandez-Fernandez, G.; Padial, L. R.; Ruilope, L. M.; Ruiz-Hurtado, G.; Barderas, M. G.
ABSTRACT: Introduction : Hypertension is a multifactorial disease that has, thus far, proven to be a difficult target for pharmacological intervention. The application of proteomic strategies may help to identify new biomarkers for the early diagnosis and prompt treatment of hypertension, in order to control blood pressure and prevent organ damage. Areas covered : Advances in proteomics have led to the discovery of new biomarkers to help track the pathophysiological processes implicated in hypertension. These findings not only help to better understand the nature of the disease, but will also contribute to the clinical needs for a timely diagnosis and more precise treatment. In this review, we provide an overview of new biomarkers identified in hypertension through the application of proteomic techniques, and we also discuss the difficulties and challenges in identifying biomarkers in this clinical setting. We performed a literature search in PubMed with the key words 'hypertension' and 'proteomics', and focused specifically on the most recent literature on the utility of proteomics in hypertension research. Expert opinion : There have been several promising biomarkers of hypertension identified by proteomics, but too few have been introduced to the clinic. Thus, further investigations in larger cohorts are necessary to test the feasibility of this strategy for patients. Also, this emerging field would profit from more collaboration between clinicians and researchers.